Preparation and Characterization of Solid Dispersions Composed of Curcumin, Hydroxypropyl Cellulose and/or Sodium Dodecyl Sulfate by Grinding with Vibrational Ball Milling - Mai, Nguyen Ngoc Sao (Pharmaceuticals (Basel), 2020)
Solubility is an important physicochemical property affecting drug bioavailability. One approach to improve drug solubility is using amorphous formulations, which can improve solubility by up to a 1000-fold. Herein, amorphous curcumin (CUR) and amorphous solid dispersions (SDs) consisting of CUR, hydroxypropyl cellulose (HPC) and/or sodium dodecyl sulfate (SDS) were developed using vibrational ball milling. The resulting ground mixtures (GMs) were characterized using powder X-ray diffractometry, Fourier transform infrared spectroscopy, differential scanning calorimetry and a dissolution test. The 60-min GM containing 90% HPC significantly increased the drug solubility. Presence of SDS in the GMs containing 90% HPC reduced the grinding duration from 60 min to 30 min in forming a ground SD that significantly increased the CUR dissolution rate. This amorphous state was stable for 30 days when stored at 40 °C/RH 75%.